(untitled) (The Pakistan Development Review, 2005)
Poverty is a situation of deprivation, failure to fulfill the minimum basic physical and psychological needs of an individual due to unavailability of sufficient economic resources at its disposal. It is associated to insufficient outcomes with respect to nutrition, health and education, to deficient social relations, to insecurity and to low self-esteem and powerlessness. So poverty can be analysed from monetary and non-monetary indicators of well-being. In Pakistan Poverty have manifold expressions, many dimensions and indeed, many root causes. Given such multidimensionality, it is not difficult to see why poverty cannot be reduced or summarily expressed, in terms of a single quantitative or qualitative indicator alone. Similarly, for alleviating poverty, all routes matter, recognising the heterogeneity of the voices and the perspectives of the poor expressed in economic and non-economic terms. Such a multidimensional approach, moreover, brings into forefront the importance of recognising the causal factors of poverty at the local level and addressing area-specific problems based on perceived needs and demands of the poor. An essential pre-requisite of institutionalising the approach, however, is the existence of decentralised and participatory structure of local governance that can introduce participatory development in which citizen at the grass-root are involved in planning, formulating and implementation of programs for themselves. In Pakistan, a local government system has been installed in the form of “Devolution Plan 2000” after the promulgation of Local Government Ordinance 2001 by all Provinces.....................